Narratives of femicide perpetrators in Latin America: taking lives - Di Marco, Martín Hernán (Palgrave Macmillan, 2025)
This book synthesises narrative research on men convicted of intimate femicide/feminicide in Latin America. Based on repeated biographical interviews conducted across eight countries, it offers a sociological exploration of the perpetrators’ lives and their processes of sense-making through the analysis of their narratives. The book identifies cross-cutting themes and narrative arcs in these men's accounts and examines how these relate to, interweave with one another, and help explain the perpetration of intimate partner violence. By deepening our understanding of harm-doing, it contributes to ongoing debates in criminology, law, public health, the social and human sciences of violence, and gender studies.